Human Vγ2Vδ2 T cells limit breast cancer growth by modulating cell survival‐, apoptosis‐related molecules and microenvironment in tumors. Issue 9 (29th May 2013) - Aggarwal, Reeva; Lu, Jingwei; Kanji, Suman; Das, Manjusri; Joseph, Matthew; Lustberg, Maryam B.; Ray, Alo; Pompili, Vincent J.; Shapiro, Charles L.; Das, Hiranmoy
Abstract : Innate immune system has been known to play an important role in inhibiting the malignant transformation, tumor progression and invasion. However, the mechanistic basis remains ambiguous. Despite polyclonality of human γδ T cells, Vγ2Vδ2 T cell subset was shown to recognize and limit the growth of various tumors at various degrees. The differential recognition of the tumor cells by Vγ2Vδ2 T cells are yet to be defined. Our study reveals that γδ T cells limit in vitro growth of most breast tumor cells, such as SkBr7 (HER2+), MCF7 (ER+) and MDA‐MB‐231 (ER−) by inhibiting their survival and inducing apoptosis, except BrCa‐MZ01 (PR+) cells. To investigate detail mechanisms of antineoplastic effects, we found that cell death was associated with the surface expression levels of MICA/B and ICAM1. Molecular signaling analysis demonstrated that inhibition of cell growth by γδ T cells was associated with the lower expression levels of cell survival‐related molecules such as AKT, ERK and concomitant upregulation of apoptosis‐related molecules, such as PARP, cleaved caspase 3 and tumor suppressor genes PTEN and P53. However, opposite molecular signaling was observed in the resistant cell line after coculture with γδ T cells. In vivo, antineoplastic effects of γδ T cells were also documented, where tumor growth was inhibited due to the downregulation of survival signals, strong induction of apoptotic molecules, disruption of microvasculature and increased infiltration of tumor associated macrophages. These findings reveal that a complex molecular signaling is involved in γδ T cell‐mediated antineoplastic effects. Abstract : What's new? Cancer growth is delayed in patients treated via the adoptive transfer of γδ T cells. The molecular mechanisms of this effect aren't clearly understood. In this study, the authors examined the signaling pathways by which the Vγ2Vδ2subset of T cells inhibit breast‐cancer cells. They found that these T cells down‐regulated survival signals, while up‐regulating apoptosis‐related molecules, both in vitro and in vivo. The γδ T cells also caused disruption of the tumor microvasculature and increased infiltration of tumor associated macrophages (TAMs). These findings may lead to targeted therapies that combine both small molecules and immune cells.